2007
DOI: 10.1111/j.1748-5827.2007.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy leads to fast improvement of haematological and immunological parameters in bitches with pyometra

Abstract: Application of immunostimulating therapy is not necessary to manage changes in blood cell counts and suppression of lymphocyte activity in bitches with pyometra. Removal of the infected uterus, being the source of infection, leads to improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
3
17
1
4
Order By: Relevance
“…This is similar to results reported by others (Kustritz, 2005;Bartoskova et al, 2007). Similarly, the 80% of bitches with high white blood cell count is consistent with other series (Kustritz, 2005;Verstegen et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…This is similar to results reported by others (Kustritz, 2005;Bartoskova et al, 2007). Similarly, the 80% of bitches with high white blood cell count is consistent with other series (Kustritz, 2005;Verstegen et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…However, the nature of this acute glomerular dysfunction still needs to be defined 6 . There are no increased levels of circulating immune complexes in dogs with pyometra compared with healthy ones 14 . Other studies reported only tubulointerstitial lesions in dogs with pyometra 6,7 or even found no histological differences between healthy dogs and dogs with pyometra 9…”
mentioning
confidence: 99%
“…Yet, the underlying changes in sex hormone levels during heat and dioestrus and subsequent physiological responses of the canine uterus are crucial for the onset and progression of pyometra (Johnston et al 2001, Noakes et al 2001Fransson and Ragle, 2003). The impaired immunological status of bitches with pyometra has already been described (Faldyna et al 2001a;Bartoskova et al 2007) but whether and to what extent sex hormones contribute to the immunological aspect (i.e. potentially altered susceptibility) of the development of this disease in bitches has remained open to question.…”
mentioning
confidence: 99%